RUANG BERKUMPUL INFORMAL ANAK DI RUSUNAWA JOGOYUDAN, KAMPUNG GOWONGAN KIDUL KECAMATAN GONDOKUSUMAN YOGYAKARTA - Ikhwanuddin, Fiterian Centauri (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This study is aimed to know the children gathering space, the physical element found in it, and factors that may affect the establishment of the children gathering space. This study applied a qualitative approach which is to depict or describe a natural condition that occurs. In collecting the data, the researchers conducted observations in the field to observe the activities of children, physical setting of children gathering space and physical elements in it. The site of this research was conducted at Rusun Jogoyudan Gowongan Kampung Kidul village, Gondokusuman sub-district, Yogyakarta. The findings of this study show that children in the gathering space rusunawa Jogoyudan, Yogyakarta including: stall / guard post, stall / gabion (river banks), the mosque yard (front and side), entrance way. Physical elements children gathering space at the towers include: a) the floor elements in form of paving blocks floor (mostly), cement pavement and gabion, b) a roof element in form of tritisan stalls and mosques and, c) the wall elements in form of fences, walls of the house / shop, gabion and embankments. Factors that may affect the establishment of the gathering space are broad view, easily accessible place and shady place, cool air, within near range of children; there are snack stalls and healthy snacks sellers. Keywords: Children gathering space, rusunawa Jogoyudan, settlemen